2012
DOI: 10.1051/0004-6361/201218816
|View full text |Cite
|
Sign up to set email alerts
|

e-MERLIN and VLBI observations of the luminous infrared galaxy IC 883: a nuclear starburst and an AGN candidate revealed

Abstract: Context. The high star formation rates of luminous infrared galaxies (LIRGs) make them ideal places for core-collapse supernova (CCSN) searches. Massive star formation can often be found in coexistence with an active galactic nucleus (AGN), contributing jointly to the energy source of LIRGs. At radio frequencies, where light is unaffected by dust extinction, it is possible to detect compact components within the innermost LIRG nuclear regions, such as SNe and SN remnants, as well as AGN buried deep in the LIRG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…This source was classified as an AGN/SB composite (Yuan et al 2010), which has been confirmed by the direct detection of a number of radio componentes that are consistent with an AGN and with SNe/SNRs (Romero-Cañizales et al 2012b) and with the detection, in the near-IR, of two SNe (Kankare et al 2012) within the innermost nuclear region of the galaxy. Through SED model fitting, RomeroCañizales et al (2012b) estimated a core collapse supernova (CCSN) rate of 1.1 SN yr −1 and a SFR of 185 M yr −1 .…”
Section: Ic 883mentioning
confidence: 56%
“…This source was classified as an AGN/SB composite (Yuan et al 2010), which has been confirmed by the direct detection of a number of radio componentes that are consistent with an AGN and with SNe/SNRs (Romero-Cañizales et al 2012b) and with the detection, in the near-IR, of two SNe (Kankare et al 2012) within the innermost nuclear region of the galaxy. Through SED model fitting, RomeroCañizales et al (2012b) estimated a core collapse supernova (CCSN) rate of 1.1 SN yr −1 and a SFR of 185 M yr −1 .…”
Section: Ic 883mentioning
confidence: 56%
“…Moreover, recent observations indicate that the SF region of Arp 193 is much more compact than indicated by low-J CO imaging (which trace both SF and non-SF molecular gas). Indeed, recent e-MERLIN and very long baseline interferometry imaging revealed recent starburst activity indicated by SNe and SNR taking place within a region with a radius of r ∼ 120 pc (Romero-Cañizales et al 2012). For such compact region, a "coherent" starburst event becomes much easier to induce.…”
Section: The Molecular Gas In Arp 193mentioning
confidence: 99%
“…The SN rate estimates from such searches are still a factor of 3-10 lower than is expected from the high star formation rates inferred from the far-IR luminosities of the surveyed galaxies (e.g., Cresci et al 2007). Radio very long baseline interferometry studies of the innermost regions of LIRGs have, in fact, revealed scores of radio SNe and supernova (SN) remnants that have remained hidden at other wavelengths (Lonsdale et al 2006;Pérez-Torres et al 2009;Ulvestad 2009;Bondi et al 2012;Herrero-Illana et al 2012;Romero-Cañizales et al 2012). A few bona fide radio transients have also been identified as obscured SNeII, e.g., an SN in the starburst Galaxy Mrk297 (Yin & Heeschen 1991), VLA 121550.2+130654 (Gal-Yam et al 2006), and SN2008iz in M82 (A V > 10 mag ;Brunthaler et al 2009Brunthaler et al , 2010Mattila et al 2013).…”
Section: Introductionmentioning
confidence: 99%